Ultra-sensitive chemical and biological analysis via specialty fibers with built-in microstructured optofluidic channels. Issue 4 (21st February 2018) - Zhang, Nan; Li, Kaiwei; Cui, Ying; Wu, Zhifang; Shum, Perry Ping; Auguste, Jean-Louis; Dinh, Xuan Quyen; Humbert, Georges; Wei, Lei
Abstract : A specialty fiber with a built-in microfluidic channel enables ultra-sensitive, low-loss and compact all-in-fiber in-line optofluidic chemical and biological sensing. Abstract : All-in-fiber optofluidics is an analytical tool that provides enhanced sensing performance with simplified analyzing system design. Currently, its advance is limited either by complicated liquid manipulation and light injection configuration or by low sensitivity resulting from inadequate light–matter interaction. In this work, we design and fabricate a side-channel photonic crystal fiber (SC-PCF) and exploit its versatile sensing capabilities in in-line optofluidic configurations. The built-in microfluidic channel of the SC-PCF enables strong light–matter interaction and easy lateral access of liquid samples in these analytical systems. In addition, the sensing performance of the SC-PCF is demonstrated with methylene blue for absorptive molecular detection and with human cardiac troponin T protein by utilizing a Sagnac interferometry configuration for ultra-sensitive and specific biomolecular specimen detection. Owing to the features of great flexibility and compactness, high-sensitivity to the analyte variation, and efficient liquid manipulation/replacement, the demonstrated SC-PCF offers a generic solution to be adapted to various fiber-waveguide sensors to detect a wide range of analytes in real time, especially for applications from environmental monitoring to biological diagnosis.